Adaptasi Pelayanan Organisasi Gereja Di Masa Pandemi: Mengunggah Dampak Pandemi Bagi Pertumbuhan Gereja - Sabda Budiman; Maharin; Hengki Wijaya (SOPHIA: Jurnal Teologi dan Pendidikan Kristen, 2022)
The COVID-19 pandemic is seen as one of the factors that can hinder the growth of the church. However, has the COVID-19 pandemic always had a negative impact on church organizations? The purpose of this study was written to observe and explain the positive impact of the pandemic on the growth of the church. The methods that researchers use are literature research methods and also field observations. This research resulted in the adaptation of church organization services for church growth during the pandemic, namely: First, Family-Based Discipleship. Second, the Virtual Church. Third, the Optimization of Church Diakonia. The Church is required to step out of her comfort zone and show her light in the middle of the world. Thus, the COVID-19 pandemic is not seen as a disaster for the church, but instead it has stimulated the growth of the church on the previously hard-to-reach side.    Pandemi COVID-19 dipandang sebagai salah satu faktor yang dapat menghambat pertumbuhan gereja. Akan tetapi, apakah pandemi COVID-19 selalu membawa dampak negatif bagi pertubuhan gereja? Tujuan dari peneitian ini ditulis ialah untuk mengamati dan memaparkan dampak positif pandemi bagi pertumbuhan gereja. Metode yang peneliti gunakan ialah metode penelitian kepustakaan dan juga pengamatan lapangan. Penelitian ini menghasilkan adaptasi pelayanan organisasi gereja untuk pertumbuhan gereja di masa pandemi yaitu: Pertama, Pemuridan Berbasis Keluarga. Kedua, Gereja Virtual. Ketiga, Optimalisasi Diakonia Gereja. Gereja dituntut keluar dari zona nyaman dan menunjukkan terangnya di tengah dunia. Dengan demikian, pandemi COVID-19  tidak dipandang sebagai musibah bagi gereja, tetapi sebaliknya pandemi ini telah merangsang pertumbuhan gereja pada sisi yang sebelumnya sulit dijangkau.